2012
DOI: 10.3389/fphar.2011.00089
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of a Leupeptin-Derived Calpain Inhibitor Fails to Ameliorate Severe Muscle Pathology in a Canine Model of Duchenne Muscular Dystrophy

Abstract: Calpains likely play a role in the pathogenesis of Duchenne muscular dystrophy (DMD). Accordingly, calpain inhibition may provide therapeutic benefit to DMD patients. In the present study, we sought to measure benefit from administration of a novel calpain inhibitor, C101, in a canine muscular dystrophy model. Specifically, we tested the hypothesis that treatment with C101 mitigates progressive weakness and severe muscle pathology observed in young dogs with golden retriever muscular dystrophy (GRMD). Young (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Histopathologic / functional correlation would be required to validate these markers and is ongoing, using functional indices of isometric distal limb force [37] and repeated eccentric contractions; muscle weight; and histopathological measures of myofiber and endomysial space (non-contractile tissue) per unit area [38, 39]. .…”
Section: Ivdiscussionmentioning
confidence: 99%
“…Histopathologic / functional correlation would be required to validate these markers and is ongoing, using functional indices of isometric distal limb force [37] and repeated eccentric contractions; muscle weight; and histopathological measures of myofiber and endomysial space (non-contractile tissue) per unit area [38, 39]. .…”
Section: Ivdiscussionmentioning
confidence: 99%
“…, Childers et al . ). Considering that multiple sarcomeric and cytoskeletal proteins, kinases and transcription factors are calpain substrates (Goll et al .…”
Section: Calpainsmentioning
confidence: 97%
“…(Childers et al . ) when they found that C101 failed to decrease calpain activity or decrease disease severity following eight weeks of treatment in golden retriever muscular dystrophy (GRMD) dogs. Additionally, 6 months of leupeptin administration did not lead to histological or functional benefits in mdx mice (Selsby et al .…”
Section: Calpainsmentioning
confidence: 99%
“…Unfortunately, long-term intravenous administration of NBD was found to induce untoward infusion reactions even in normal dogs. In addition to anti-inflammatory drugs, CXMD dogs have also been used to test calpain inhibitor (172), proteasome inhibitor (173), bradykinin (174,175), and laminin-111 protein therapy (176). Proteasome inhibitor reduced muscle inflammation and partially restored dystrophin-associated glycoprotein complex.…”
Section: Therapeutic Testing In the Canine Model And Impact On Patienmentioning
confidence: 99%